2013
DOI: 10.1371/journal.pone.0081256
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Nationwide Cross-Sectional Study on Preventive Health Services Utilization in Portugal—What Services (and Frequencies) Are Deemed Necessary by Patients?

Abstract: BackgroundMost of the strategies to induce a more rational use of preventive health services are oriented to the medical side of the doctor-patient relationship. However, the consultation model has changed, and patients now have a more important role in medical consultation. The aim of this study was to assess which healthcare services are deemed necessary, and with what frequency, by adults from the general Portuguese population.Methods Design: Population-based nationwide cross-sectional study Setting: Portug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 14 publications
0
36
0
5
Order By: Relevance
“…Other studies have found that costs and insurance coverage heavily influence healthcare usage, including for preventive services, in systems where healthcare costs are borne by users,7 10–12 but are less important in countries with tax-based health systems that do not impose charges on end users 40 41. Singapore's health system operates on the principles of universal health insurance with copayment by end users, so cost could still be a factor especially for those at the lower end of the socioeconomic spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that costs and insurance coverage heavily influence healthcare usage, including for preventive services, in systems where healthcare costs are borne by users,7 10–12 but are less important in countries with tax-based health systems that do not impose charges on end users 40 41. Singapore's health system operates on the principles of universal health insurance with copayment by end users, so cost could still be a factor especially for those at the lower end of the socioeconomic spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…13 Com este estudo verificou-se que mais de metade dos médicos ainda prescreve AR, o que não está de acordo com as recomendações atuais que defendem não existir benefício (mas sim um potencial aumento do risco de causar dano) para o doente na requisição de AR. 6 Impôs-se a necessidade de realizar um estudo qualitativo para apurar os motivos que levam à manutenção desta má prática nomeadamente explorar se existe uma perversão da relação médico--doente na qual o médico não tenha poder para fazer face a questões culturalmente instituídas.…”
Section: Discussionunclassified
“…5 Em Portugal a maioria dos adultos considera necessário a realização quase anual de um grande número de exames médicos e a maior parte indica que estes lhes são prescritos. 6 Na prática de Medicina Geral e Familiar (MGF), continua a não se verificar consistência entre médicos relativamente à avaliação complementar requerida para efetuar um controlo de "rotina".…”
Section: Introductionunclassified
“…Evidence shows a tendency to overuse preventive health services. 2,3 In Portugal, for example, a recent population-based cross-sectional study showed that the majority of Portuguese adults think they should undergo general routine blood and urine tests on an annual basis. Other, even less-recommended screening tests, such as lung X-rays, breast ultrasounds, abdominal ultrasounds, and gynaecological ultrasounds, are deemed necessary by a great proportion of the population.…”
mentioning
confidence: 99%
“…Other, even less-recommended screening tests, such as lung X-rays, breast ultrasounds, abdominal ultrasounds, and gynaecological ultrasounds, are deemed necessary by a great proportion of the population. 3 In part, this pattern of behaviour may be justified by the culturally-rooted idea that routine general health checks are necessary. Obtaining general health checks is a practice that is not supported by evidence -it does not reduce morbidity or mortality, neither overall nor from cardiovascular or cancer-related illnesses, although they can increase the number of new diagnoses.…”
mentioning
confidence: 99%